Moult strategies and morphometric precisions in the Lilford's woodpecker Dendrocopos leucotos lilfordi (Avocetta, 2024)
This article presents a study of the plumage of the Lilford's woodpecker Dendrocopos leucotos lilfordi. The species performs a partial post-juvenile moult for the first-year birds and a complete post-nuptial moult regularly arrested for adults. The criteria presented make it possible to differentiate the two age-classes of a bird in hand. Furthermore, a difference in wing shape via the wing formula appears between females and males, suggesting a different internuptial or post-juvenile dispersal behaviour depending on the sexes.
Keywords: post juvenile moult; post nuptial moult; wing formula